2018
DOI: 10.3390/rs10030419
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave Radiation Affected by Agricultural Practices

Abstract: Abstract:The albedo of bare soil depends on its organic matter, iron oxide, carbonate contents, and reflectance geometry, features considered stable over time, and also depends on salinity, moisture and roughness, which change dynamically due to agricultural practices. This paper deals with the quantitative estimation of the amount of shortwave radiation that could be reflected by air-dried bare soils in clear-sky conditions within arable lands in Israel throughout the year, assuming that they were shaped by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The BS on the global scale ( Fig. 2a,b) provides strong evidence of land disturbance, contributing to the discussion of its consequences, such as erosion 39 and changes in energy balance/climate/emissivity 40,41 , temperature 42 , moisture 43 , SOC stocks 1 and microorganism populations 44 . In addition, an increase in BSF may promote greater weed growth 45 , which may intensify pesticide use 46 and, consequently, groundwater contamination 47 .…”
Section: Results and Disscussionmentioning
confidence: 95%
“…The BS on the global scale ( Fig. 2a,b) provides strong evidence of land disturbance, contributing to the discussion of its consequences, such as erosion 39 and changes in energy balance/climate/emissivity 40,41 , temperature 42 , moisture 43 , SOC stocks 1 and microorganism populations 44 . In addition, an increase in BSF may promote greater weed growth 45 , which may intensify pesticide use 46 and, consequently, groundwater contamination 47 .…”
Section: Results and Disscussionmentioning
confidence: 95%
“…The first approximations of a quantitative estimation of shortwave radiation reflected from bare arable lands illuminated at clear-sky conditions, concerning Poland (Cierniewski et al 2017) and Israel (Cierniewski et al 2018b), based on extracting their changing areas during the year from Landsat 8 images. It was found that these areas reach two maxima in spring and late summer in Poland and one maximum in summer until early autumn in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the α variations of bare soils discussed above, as well as the statement of Sellers et al (1995) about the acceptable error lower than ± 2% of α of the Earth's land surfaces for modeling climate changes on a global scale, the use of their average diurnal (α d ) values or the averaged values over longer periods of several days, a month, a season, or a year for this modeling seems to be more useful than the use of instantaneous α values (Grant et al 2000;Cierniewski et al 2014). So far, the α d values of bare soils have also been used to estimate the annual dynamic of shortwave radiation reflected from bare soils as a consequence of the smoothing of previously plowed and disk-harrowed fields in Poland (Cierniewski et al 2017) and reflected from arable lands in Israel (Cierniewski et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cierniewski et al (2018a) proposed a set of equations that could be used to calculate the diurnal variation of bare soil a, using 153 sets of soil surface measurements collected from Poland, Israel and France. The equations are used as the input data for θ s. In contrast with the procedure adopted in the study by Ziar et al (2019), these measurements require only few simple free parameters: specific roughness, and reflectance values of soils.…”
Section: Introductionmentioning
confidence: 99%